Upaya Program Studi Pendidikan Agama Islam dalam Meningkatkan Prestasi Akademik Mahasiswa Angkatan 2021 di Universitas Islam Negeri Sumatera Utara - Rizky Indira Nasution; Arlina (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The academic achievement is a benchmark for human resources. Graduates with quality demonstrate that they are actively engaged in learning; sometimes, there are students who graduate with satisfactory results. Academic achievement is essential to facilitate job searching and apply the acquired knowledge in the workplace. This research was conducted at the State Islamic University of North Sumatra (UINSU) in the Islamic Education Program and involved several students. The method employed was through interviews. The backgrounds of the students varied, including those who work, those who are actively involved in organizations, and those who neither work nor participate in any organizations. The academic achievements of several interviewed students were outstanding with a Cumulative Grade Point Average (CGPA) of 'Cum Laude.' It is hoped that the field of education will be of high quality.